STRATEGI PEMULIHAN PASCABENCANA ERUPSI MERAPI BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KETAHANAN WILAYAH DI KABUPATEN SLEMAN - Dwi Jati Marta (Pangripta Sembada : Jurnal Perencanaan Pembangunan, 2025)
This study aims to analyze post-disaster recovery strategies following the Merapi eruption in Sleman Regency through a regional resilience approach grounded in local wisdom. A qualitative, hermeneutic-philosophical method was applied to interpret the deeper meaning behind social practices and cultural values of Merapi communities in disaster response. Data were collected through literature studies and analyzed using NVivo 12 Plus to map social, economic, and cultural resilience indicators. The results indicate that Merapi communities demonstrate strong social resilience through communal solidarity and the value of guyub rukun, economic resilience through tourism-based adaptation, and cultural resilience through the preservation of rituals and the hamemayu hayuning bawana philosophy. The integration of local wisdom with government policy effectively strengthens a more inclusive and sustainable disaster management system. Therefore, continued synergy between traditional knowledge and modern innovation is essential to enhance community resilience in volcanic hazard-prone areas.